The underappreciated contribution of Oskar Fischer to the knowledge of Frontotemporal Lobar Degeneration - Eliasz Engelhardt; Lea Tenenholz Grinberg (Dementia & Neuropsychologia)
ABSTRACT Frontotemporal Lobar Degeneration (FTLD) encompasses progressive neurodegeneration primarily affecting the frontal and/or temporal lobes, presenting in varied pathological entities. These pathologies lead to diverse clinical syndromes collectively known as Frontotemporal Dementia (FTD), which includes a behavioral variant, and primary progressive aphasia, with its non-fluent and semantic variants, and related conditions with parkinsonism or motoneuron disease features. The historical development of FTD concept is rooted in the pioneering work of Arnold Pick, who first described clinical cases of focal brain atrophy. Oskar Fischer significantly advanced this field by detailing the histopathological features of these conditions, such as the ‘spongiform cortical wasting’, and identifying characteristic neuronal changes such as the ‘ballooned cells’. Fischer’s contributions, alongside those of contemporaries like Alois Alzheimer, laid the foundation for understanding FTLD histopathology. Here, Fischer’s overlooked work is spotlighted, advocating for a greater recognition, which he rightfully deserves for his contributions to the field of neurodegenerative diseases.